2016
DOI: 10.1002/hon.2278
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of chronic lymphocytic leukemia occurring in chornobyl cleanup workers

Abstract: The recently demonstrated radiation-induction of chronic lymphocytic leukemia (CLL) raises the question as to whether the amount of radiation exposure influences any of the clinical characteristics of the disease. We evaluated the relationship between bone marrow radiation doses and clinical characteristics and survival of 79 CLL cases diagnosed during 1986–2006 in a cohort of 110,645 male workers who participated in the cleanup work of the Chornobyl nuclear accident in Ukraine in 1986. All diagnoses were conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…In addition to CLL risk estimates, it was defined that older age at first exposure, smoking, and higher frequency of visits to the doctor were significantly associated with a shorter latent period. At the same time, the association of radiation dose and younger age at first radiation exposure at Chornobyl with shorter survival after diagnosis was shown, though not statistically significant [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CLL risk estimates, it was defined that older age at first exposure, smoking, and higher frequency of visits to the doctor were significantly associated with a shorter latent period. At the same time, the association of radiation dose and younger age at first radiation exposure at Chornobyl with shorter survival after diagnosis was shown, though not statistically significant [27].…”
Section: Discussionmentioning
confidence: 99%
“…48 More recent epidemiologic studies have implicated radiation at Chernobyl in CLL risk among clean-up workers, 49 and suggested a dose-dependent increase in the risk of death from CLL in this population. 50 Systematic studies on other environmental exposures are limited. A case-control study from Germany investigated occupational risk factors for high-grade lymphoma, low-grade lymphoma, or CLL.…”
Section: Environmental Risksmentioning
confidence: 99%
“…We also recently reported that higher radiation doses and younger age at first exposure to radiation during Chernobyl cleanup work were associated with significantly shorter survival of CLL cases. 21 The median age at diagnosis was 57 years compared to the median age at diagnosis in the U.S. of 72 years. 22 Further investigations are needed to develop a better understanding of the association between radiation and CLL, which is the most common type of leukemia in this cleanup worker population.…”
Section: Leukemia In Chernobyl Cleanup Workersmentioning
confidence: 99%